2009
DOI: 10.1016/j.gloplacha.2009.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of Late Cenozoic sediments of the western Chukchi Sea: New results from shallow drilling and seismic-reflection profiling

Abstract: The Quaternary history of Beringia and of the Arctic-Pacific marine connection via the Bering Strait is poorly understood because of the fragmentary stratigraphic record from this region. We report new borehole and seismic-reflection data collected in 2006 in the southwestern Chukchi Sea. Sediment samples were analyzed for magnetic properties, grain size, heavy minerals, and biostratigraphic proxies (spores and pollen, foraminifers, ostracodes, diatoms, and aquatic palynomorphs). Two shallow boreholes drilled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…We suggest that the reflector is relict seafloor permafrost that formed when sea level was much lower juxtaposed on a more modern layer of non-permafrost marine sediment. According to seismo-stratigraphic data reported in Gusev et al (2009), a similar seismic reflector was identified south of Wrangel Island and offshore the Chukotka Peninsula. This reflector is interpreted to be the Pleistocene-Holocene boundary on the basis of radiocarbon dating and borehole lithostratigraphy.…”
Section: Specific Features Of Gascontaining Sedimentsmentioning
confidence: 57%
See 2 more Smart Citations
“…We suggest that the reflector is relict seafloor permafrost that formed when sea level was much lower juxtaposed on a more modern layer of non-permafrost marine sediment. According to seismo-stratigraphic data reported in Gusev et al (2009), a similar seismic reflector was identified south of Wrangel Island and offshore the Chukotka Peninsula. This reflector is interpreted to be the Pleistocene-Holocene boundary on the basis of radiocarbon dating and borehole lithostratigraphy.…”
Section: Specific Features Of Gascontaining Sedimentsmentioning
confidence: 57%
“…Study of sediment cores and seismic stratigraphy provide deposition patterns and sedimentation rates for the Chukchi Sea (Gusev et al, 2009(Gusev et al, , 2014. For the western part of this sea, Gusev et al (2009) report relatively high early Holocene sedimentation rates of several meters per thousand years, which are common for the early stages of flooding on the Arctic shelf (e.g., Stein et al, 2004).…”
Section: Sedimentation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…), and Chukchi Sea (Gusev et al . ). Sediment units defined by unconformities are called unconformity‐bounded units in the International Stratigraphic Guide (Salvador ) and Lithuanian Stratigraphic Guide (Grigelis et al .…”
mentioning
confidence: 97%
“…Chukchi Sea receives many sediment loads from the peripheral continental rivers, the Pacific inflow, and sea ice transport (Viscosi-Shirley, Pisias, and Mammone 2003;Eicken et al 2005). The thickness of sediments can reach 20 to 22 km (Gusev et al 2009). These geomorphic features are controlled by the graben rift system that started in the Mesozoic (Shipilov 1989;Shipilov and Senin 1992).…”
Section: Introductionmentioning
confidence: 99%